Aquipluma nitroreducens gen. nov. sp. nov., a novel facultatively anaerobic bacterium isolated from a freshwater lake. Issue 12 (6th December 2020) - Watanabe, Miho; Kojima, Hisaya; Fukui, Manabu
Abstract : A novel facultatively anaerobic, nitrate-reducing bacterium, designated MeG22 T, was isolated from a freshwater lake in Japan. Cells of the strain were straight rods (0.8×2.5–10 µm), motile, and Gram-stain-negative. For growth, the optimum NaCl concentration was 0 % and the optimum temperature was 30 °C. Under anoxic conditions, strain MeG22 T reduced nitrate to nitrite. Major cellular fatty acids were C15 : 1 ω6 c (13.6 %), C17 : 0 (11.9 %), anteiso-C15 : 0 (10.6 %) and iso-C15 : 0 (10.6 %). The major respiratory quinone was menaquinone-7. The genome sequence of strain MeG22 T consists of 5 712 279 bp with a G+C content of 40.3 mol%. Phylogenetic analysis based on the 16S rRNA gene revealed that the novel strain belonged to the family Prolixibacteraceae within the phylum Bacteroidetes . The closest relative of strain MeG22 T was Sunxiuqinia faeciviva strain JAM-BA0302 T with a 16S rRNA gene sequence similarity of 90.9 %. On the basis of phylogenetic and phenotypic characterization, Aquipluma nitroreducens, gen. nov., sp. nov., belonging to the family Prolixibacteraceae is proposed with the type strain MeG22 T (=NBRC 112896 T =DSM 106262 T ).